The Relationship Between Family Support and Compliance of Pregnant Women in the Second Trimester in Consuming Iron (Fe) Tablets in the Working Area of the Mandomai Public Health Center - Christina Dewi; Widia Shofa Ilmiah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Anemia during pregnancy remains a major public health concern and is commonly associated with iron deficiency. Iron (Fe) tablet supplementation is a key strategy to prevent anemia; however, adherence among pregnant women remains suboptimal. This study aimed to analyze the relationship between family support and adherence to iron tablet consumption among second-trimester pregnant women in the working area of UPT Puskesmas Mandomai. A quantitative analytic study with a cross-sectional design was conducted involving 30 pregnant women selected using total sampling. Data were collected using a structured questionnaire assessing respondents’ characteristics, family support, and adherence to iron tablet consumption. Univariate analysis was performed to describe variable distributions, while bivariate analysis was conducted using Kendall’s tau-b correlation test. The results showed that 50% of respondents were non-adherent to iron tablet consumption, and 50% reported receiving no family support. Bivariate analysis revealed a statistically significant and very strong association between family support and adherence to iron tablet consumption (τ = −0.928; p < 0.001). The negative correlation reflected the coding direction, indicating that better family support was associated with higher adherence. These findings suggest that family support plays an important role in promoting adherence to iron supplementation during pregnancy. Family-centered approaches in antenatal care may enhance adherence and contribute to the prevention of anemia among pregnant women.